The reporter and the law : - Denniston, Lyle W. (Columbia University Press, 1992)
The Reporter and the Law is an insider's view of how the legal system and the press work together. Lyle Denniston begins from the premise that the law and its institutions are the public's business and that the journalist's responsibility is to appreciate, understand, and evaluate the legal process and to convey that reasoned comprehension to the public. To facilitate this task, Denniston dispels the cloud of mystery that surrounds legalese, defines the jargon of both the legal and the journalistic professions, and explains how each discipline depends on the other to perform its task properly. The first part of The Reporter and the Law explains the framework of the legal process, describes various methods a legal reporter may use to develop sources, and suggests how a reporter can live productively within the system of jurisprudence. The remainder of the book is a detailed "how to" manual which is beneficial to both the journalism student and the experienced reporter. Denniston carefully describes the best ways for a journalist to cover a trial and he analyzes each structural element of the trial for its optimum news potential.